The long-run performance of firms that issue convertible debt: an empirical analysis of operating characteristics and analyst forecasts - Lewis, Craig M; Rogalski, Richard J; Seward, James K (Journal of Corporate Finance, 2001)
Many firms issue hybrid securities, such as convertible debt, instead of standard securities like straight debt or common equity. Theoretical arguments suggest that convertible debt minimizes costs for firms facing high debt- and equity-related external financing costs. Theory also suggests that an appropriately designed convertible security provides efficient investment incentives. We show, however, that firms on average perform poorly following the issuance of convertible debt. The empirical evidence suggests that the efficient investment decisions predicted by theory are not in fact achieved by the actual design and issuance of convertible debt securities. An alternative interpretation of convertible debt offers is that investors ration the participation of some issuers in the seasoned equity market.